2019
DOI: 10.1002/hbm.24581
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of vibrotactile categorization

Abstract: The grouping of sensory stimuli into categories is fundamental to cognition. Previous research in the visual and auditory systems supports a two‐stage processing hierarchy that underlies perceptual categorization: (a) a “bottom‐up” perceptual stage in sensory cortices where neurons show selectivity for stimulus features and (b) a “top‐down” second stage in higher level cortical areas that categorizes the stimulus‐selective input from the first stage. In order to test the hypothesis that the two‐stage model app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The first stage is a “bottom-up” stage where neurons in the sensory cortices learn to respond to stimulus features while the second stage is a “top-down” stage where neurons in higher cortical areas learn to classify the stimulus-selective inputs from the first stage. To investigate whether the two-stage processing hierarchy also exists in the somatosensory system, Malone et al (2019) designed an experiment where human participants, after training to label vibrotactile stimuli presented to their right forearm, underwent an fMRI scan while actively engaging in categorizing the stimuli. The authors first applied representational similarity analysis to identify the stimulus- and category- selective areas.…”
Section: Biophysical Network Modelmentioning
confidence: 99%
“…The first stage is a “bottom-up” stage where neurons in the sensory cortices learn to respond to stimulus features while the second stage is a “top-down” stage where neurons in higher cortical areas learn to classify the stimulus-selective inputs from the first stage. To investigate whether the two-stage processing hierarchy also exists in the somatosensory system, Malone et al (2019) designed an experiment where human participants, after training to label vibrotactile stimuli presented to their right forearm, underwent an fMRI scan while actively engaging in categorizing the stimuli. The authors first applied representational similarity analysis to identify the stimulus- and category- selective areas.…”
Section: Biophysical Network Modelmentioning
confidence: 99%
“…1A) used a frequency-to-place mapping algorithm: The energy passed by each filter of the vocoder was used to modulate the vibration of a specific MRI-compatible transducer on the 16-channel VT device (Fig. 1A and 1C) placed on the volar forearm (Malone et al, 2019). Low frequencies mapped to transducers near the wrist, and higher frequencies mapped to transducers near the elbow.…”
Section: Vt Vocoded Speech Encodingmentioning
confidence: 99%
“…Recent studies using vibrotactile stimuli to examine cognitive processes have proven reliable in eliciting responses from somatosensory areas. The vibrotactile stimuli have been applied to young adults in areas such as bilateral fingertips (Chung et al, 2013;Goltz et al, 2013;Puckett et al, 2017;Seri et al, 2019Seri et al, , 2020, digits fingertips (Francis et al, 2000;Pfannmöller et al, 2016;Schweisfurth et al, 2011Schweisfurth et al, , 2014Schweisfurth et al, , 2015, right forearms (Malone et al, 2019), breast (Beugels et al, 2020), leg and foot (Akselrod et al, 2017), sole of the right foot (Siedentopf et al, 2008), and the chest, chin and arm (Jung et al, 2018). Similarly, it was observed that the vibrotactile stimulation using a piezoelectric stimulation system shows good congruency in the S1 cortex using fMRI (functional magnetic resonance imaging) response location (Jaatela et al, 2022), thus proving the reliability of vibrotactile as a stimulus to evoke responses in the somatosensory areas.…”
Section: Introductionmentioning
confidence: 99%